The penitentiary institution 'Veenhuizen' at Norg (Bulletin KNOB, 1992)
With the support of King William l and private persons the military man Johannes van den Bosch (1780-1840) founded the Benevolent Society in 1818. This Society aimed at exploitation of wasteland by socially weak groups so that afterwards these could provide their means of support themselves. This way the individual man would obtain a more human existence while also on a national level economical prospects would improve.In Veenhuizen at Norg in the province Drenthe the Society founded a colony for exploitation. Soon the ideal did not prove to be equal to hard reality. In 1859 the State took charge of the Benevolent Society. Meanwhile the character of the colony for exploitation changed into a penitentiary institution (1875). At the moment the infrastructure of the old colony still is present clearly, but most of the original buildings have disappeared.At the end of the 19th century the engineer-architects J.F. Metzelaar (1818-1897) and his son W.C. Metzelaar (1848-1918) designed different houses for Veenhuizen with preservation of the extant historical structure. The present complex Veenhuizen consists of farmlands, roads, canals and buildings and is an interesting challenge to the Dutch Ancient Monuments Department. At the moment State, province and municipality think about an appropriate development plan, whereby the historical character and future functional development can be adequately integrated.